Critical Drought Characteristics: A New Concept Based on Dynamic Time Period Scenarios - Abu Arra, Ahmad; Birpinar, Mehmet Emin; Gazioglu, Sukru Ayhan; Sisman, Eyup (MDPI, 2024)
In research on monitoring drought events, analysis is often carried out using a single period as a reference. On the other hand, changing this default period in drought calculations causes the drought index values obtained from research to differ. As a gap in the literature, this point highlights the necessity of investigating the effect of various time periods on drought characteristics. It underscores the need to propose a new concept and methodology to address this gap effectively. This research aims to analyze critical drought characteristics through dynamic time period scenarios. For the first time in the literature, drought indices and potential and critical characteristics were analyzed for various (dynamic) time periods. Drought analysis was carried out for 13 time period scenarios with 10-year intervals from a meteorological station in Durham (1872-2021) by changing the initial time condition using the Standardized Precipitation Index (SPI). The results showed that in addition to the similarities, there are significant differences between drought characteristics. For example, in some time period scenarios, a drought event was recorded during a specific period, while in other scenarios (S5-S7, S10-S13), no drought was detected during the same period, like in SPI 1. Additionally, for SPI 12, the drought duration varied significantly, lasting between 20 and 29 months, and for SPI 6, the drought duration varied between 3 and 13 months. Regarding the intensity, SPI 1 ranged between -0.89 and -1.33, indicating a 33% difference, and the SPI 3 intensity ranged between -1.08 and -1.91, indicating a 50% increase in intensity. This research significantly contributes to the field by providing a novel approach using dynamic time period scenarios to determine critical drought characteristics, offering valuable insights for water resource management, drought mitigation planning, and design purposes.
Keywords: potential drought characteristics; critical drought; drought evaluation; standardized precipitation index (SPI); dynamic; HOMOGENEITY; SPI; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences